Problematic Aspects of Regulating the Object of the Right to Property in Lithuania - Kadys, Eimantas (Teisė, 2022)
This paper analyzes the regulation of the object of the right to property in Lithuania and related issues. The first part of the article analyzes the concept of the object of civil property law, revealing a different understanding of the object of property law in the doctrines of property law and in the legal systems of foreign countries. The second part of this paper provides a detailed account of the regulation of the object of civil property law in Lithuania, distinguishes and elaborates the criteria according to which an object is recognized as an object in the legal sense, and articulates the features according to which intangible objects should be classified as “other property” and considered as objects of property law.
Keywords: object of property law; thing; res corporales; intangible assets; res incorporales